The Implementasi Kurikulum Merdeka dalam Proses Pembelajaran di SMA Negeri 3 Surakarta - Noik Cahya Baity; Ghufronudin Ghufronudin; Yosafat Hermawan Trinugraha (Universitas Negeri Padang, 2023)
The implementation of the Independent Curriculum is still the pros and cons in society, especially in the sphere of education. The purpose of this study was to find out how the implementation of the Independent Curriculum in the learning process at SMA Negeri 3 Surakarta. This research was examined using the concept of liberation education by Paulo Freire. This type of research is a qualitative research with a case study approach. The informant collection technique was carried out through purposive sampling and snowball sampling with informants including teachers, students, and the deputy head of curriculum. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The data that has been collected is then tested using source triangulation and analyzed using interactive analysis, including data reduction, data presentation, and drawing conclusions. The results of the study show that there are three stages towards implementing the Independent Curriculum, namely preparation, implementation, and evaluation. The Independent Curriculum is felt to be in line with liberation education because it embodies the goals of the Independent Curriculum concept, in which students and teachers carry out learning in a dialogic manner and are free to express opinions. The implementation of the Independent Curriculum in the learning process at SMA Negeri 3 Surakarta has been going quite well, although it is still not perfect. Therefore, schools do not forget to carry out evaluations in the hope that the Independent Curriculum will run even better in the future.